Development of a Social Studies Learning Model Based on Local Wisdom to Improve Cultural Literacy of Elementary School Students - Unimuda, Mursalim; Maftuh, Bunyamin; Supriatna, Mamat; Anakotta, Raisa (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
The objective of this research is to develop a learning model based on local wisdom to enhance cultural literacy among elementary school students. This study employs a Research and Development (R&D) method, adapted from Borg & Gall into five stages, namely: (1) initial information gathering (literature review and field needs analysis); (2) planning (drafting the model); (3) initial product validation (expert validation); (4) preliminary testing (small group); and (5) field testing (large group). The research subjects consisted of 6 experts and practitioners for validation, 13 teachers, and fifth-grade students comprising 90 for the instrument trial and 125 students for the limited and broader tests to assess the effectiveness of the developed learning model. Data were collected through validation sheets, interview guidelines, and student assessment sheets. The model’s validity was analyzed qualitatively, while its effectiveness was analyzed quantitatively using a paired sample t-test and N-Gain. The results showed that the social studies learning model based on local wisdom, rooted in the maataa tradition, was deemed feasible for use, with an average validator score of 3,52, falling within the range of 3,2–4,0, categorized as highly feasible. The t-test result showed a significance value of 0.000, which is less than 0,05, indicating that the maataa tradition-based local wisdom model is effective in enhancing students’ cultural literacy skills. This is evidenced by a significant improvement in students’ cultural literacy, with an average pretest score of 73,44 rising to 94.5 in the posttest. The N-Gain calculation of 0,78 places this improvement in the